Prediction of Coronary Heart Disease on Civil Servants in Jember by Framingham Risk Score - Muhammad Nadzir A. Akbar; Suryono Suryono; Aris Prasetyo; Ricky Roosdiana Dewi (Journal of Agromedicine and Medical Sciences, 2023)
Coronary heart disease is one of the biggest causes of death in developing countries. Civil servants (PNS) are a group of people who are susceptible to the disease because of their busy lives. Framingham risk score (FRS) can predict the occurrence of coronary heart disease in the next 10 years. The purpose of this study was to determine the prediction of coronary heart disease for the next 10 years in civil servants in Jember Regency. This type of research is descriptive observational with a cross sectional design. The data was taken from the medical records of patients with echelon II and III civil servants who did a medical sheck up at Dr. Soebandi Hospital in December 2013. Prediction of coronary heart disease for the next 10 years using the FRS method. From 63 medical record data, the prediction results of coronary heart disease in civil servants were 76.2% low risk, 17.5% moderate risk, and 6.3% high risk. Keywords: coronary heart disease, civil servants, framingham risk score